Is It Rational to Rear Crossbred Cow in the Hills of Meghalaya? Economics of Milk Production - Feroze, S. M.; Singh, Ram (Indian Journal of Hill Farming, 2018)
The present paper tries to find out whether the crossbred cow is economically viable in the hills of Meghalaya. Primary data were collected from 300 dairy farmers in 2013-14. The analysis revealed that share of feed cost was maximum in the total variable cost and it was followed by labour cost in case of local and CB cows in both the districts. The rearing of local cows for milk production is economically unviable whereas, the crossbred cows are economically viable at least in the short-run. Hence, it is recommended that government should encourage for rearing of CB in Meghalaya as it has the potential to augment income of rural households of the hill region.